READING INTEREST STUDIES AT STUDENT IN INDONESIAN LITERATURE AND LANGUAGE EDUCATION DEPARTMENT, AHMAD DAHLAN UNIVERSITY - Kurniawan, Muhammad Ardi; Haryadi, Haryadi; Sulistiyono, Roni (Universitas Hamzanwadi, 2020)
This study aims to determine the level of interest in reading, factors that affect interest in reading, and the type of reading PBSI UAD students. The method used in this research is the mix method. Data obtained using instruments in the form of observation sheets, interview guidelines, and questionnaires. Data collected through the process of observation, interview activities, and filling out the questionnaire. Data collected in the form of quantitative and qualitative data. The results of this study indicate that the reading interest of PBSI UAD students is categorized as low. This is known from the results of a survey that showed that 51.6% of PBSI UAD students had the frequency of reading one book per month. Other results show that the factors that influence the reading interest of PBSI UAD students are family, school, and environmental factors. Friendship Related to the variety of reading, it can be formulated that the reading consumed by PBSI UAD students can be quite broad and varied. These readings include books, magazines and social media.Keywords: factors forming reading interest, students, reading, reading interest, PBSI UAD